Multifunctional Spirocyclic Systems - Boris Lukyanov; Gennadii Vasilyuk; Eugene Mukhanov; Leonid Ageev; Maria Lukyanova; Yury Alexeenko; Serguei Besugliy; Valeri Tkachev (International Journal of Photoenergy)
New spiropyrans with different substituents in the benzopyran fragment have been synthesized and investigated. It was shown that introduction of aldehyde group in the structure of spiropyrans gives a possibility to obtain new functionalized compounds. Effects of the substituents on the photochromic behavior were studied.